224k views
1 vote
Rearrange the equation so w is the independent variable.
-2u+6w = 9


User Jahooma
by
5.2k points

2 Answers

3 votes

Answer:

u = 3w - 4.5

Explanation:

Look at attachment:

Hope this helps!

Rearrange the equation so w is the independent variable. -2u+6w = 9 ​-example-1
User Phatskat
by
4.7k points
1 vote

Answer:

u = 3w-4.5

Explanation:

w being the independent variable assumes that u will become the dependent variable. Therefore the equation needs to turn into u = aw + b

-2u + 6w = 9

*subtract 6w from both sides

-2u = 9-6w

*divide both sides by -2

u = -4.5+3w

*rearrange to make it look nicer

u = 3w-4.5

therefore: the w value doesn't care what the u value is making it independent but the u value will change from the w value making it dependent

User Nicolas Menettrier
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.